2001
DOI: 10.1001/archotol.127.12.1441
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PTEN Expression as a Prognostic Marker for Tongue Cancer

Abstract: Although genetic alterations of the PTEN gene are rare in head and neck squamous cell carcinoma, loss of PTEN is not an uncommon event in squamous cell carcinoma of the tongue. Lack of PTEN expression may be an independent prognostic indicator for clinical outcome in patients with this tumor type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
1
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 16 publications
8
100
1
7
Order By: Relevance
“…26 Other authors have reported that loss of PTEN protein expression is not uncommon and has been shown to be an independent predictive factor of poor outcome in tongue cancers. 27 Regarding allelic losses affecting PTEN gene, our results are in agreement with those reported by others on HNSCC cell lines and primary tumors. 28 No significant differences in the rate of 10q23 LOH were found with respect to any clinicopathological feature, which differs from the specific association between loss of genetic material on 10q and nodal metastasis reported in a CGH study on HNSCC.…”
Section: Discussionsupporting
confidence: 92%
“…26 Other authors have reported that loss of PTEN protein expression is not uncommon and has been shown to be an independent predictive factor of poor outcome in tongue cancers. 27 Regarding allelic losses affecting PTEN gene, our results are in agreement with those reported by others on HNSCC cell lines and primary tumors. 28 No significant differences in the rate of 10q23 LOH were found with respect to any clinicopathological feature, which differs from the specific association between loss of genetic material on 10q and nodal metastasis reported in a CGH study on HNSCC.…”
Section: Discussionsupporting
confidence: 92%
“…Previously unknown somatic mutations in 79 primary squamous cell carcinomas include recurrent E322K substitutions in the MAPK1 gene (8%), inactivating mutations in the HLA-B gene (9%), and mutations in EP300 (16%), FBXW7 (15%), NFE2L2 (4%), P53 (5%) and ERBB2 (6%). The association of poor prognosis with PTEN aberration has also been reported previously in glioma 41 and tongue carcinoma 42 . Whether PTEN methylation contributes to the development of cervical cancer and affects the prognosis has not been elucidated.…”
Section: Referencessupporting
confidence: 72%
“…29,30 These reports, however, did not elucidate whether or not the increased activity of AKT could be directly related to the resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%